Gradation reconstruction of uranium heap leaching tailings and its impact on filling performance - Fulin Wang; Ziyang He; Lou Wang; Chongxi Xu; Xinyang Geng (Case Studies in Construction Materials)
When uranium heap leaching tailings (UHLT) are used as filling aggregates, their discontinuous and non-uniform grading characteristics can easily cause segregation, settlement of the filling slurry, and deterioration of cemented body mechanical properties, seriously affecting the safety of the filling system and filling quality. To address the bimodal distribution defects of UHLT, characterized by excessively high proportions of coarse and fine particles with a lack of intermediate particle sizes, this study simulated its particle size characteristics using inert materials such as loess, fine sand, sand, and gravel. The study systematically verified the impact of grading defects on flow stability and mechanical properties. The filling slurry exhibited a spread of 222.5 mm with obvious segregation, and the uniaxial compressive strength at 28 days was 9.09 MPa. To overcome this bottleneck, this research innovatively proposed optimization strategies of qualitative reconstruction (QLR) and quantitative reconstruction (QTR). QLR involves adding medium-sized particles in stages and replacing equal amounts of coarse and fine particles, reducing the spread to 202.7 mm under an optimized quantity of 50 g, with a uniaxial compressive strength of 6.84 MPa at 3 days. However, slurry segregation still occurred. QTR established a multi-particle-size independent calculation model based on the extended Talbot gradation theory, and through the staged quantitative reconstruction of UHLT with aggregate having a grading index of 0.4, the spread decreased to 168.4 mm without segregation, achieving a uniaxial compressive strength of 5.58 MPa at 3 days and 9.11 MPa at 28 days. The study shows that both QLR and QTR can effectively improve the grading of UHLT, with QLR being simple and QTR offering precise control. The research provides new approaches for regulating filling slurries with similar discontinuous and non-uniform graded aggregates, and its innovative methodology can be extended to multiple fields such as concrete aggregate optimization.